The Relationship Between Pregnant Women's Satisfaction With Antenatal Care And The Regularity Of Antenatal Check-Ups At The Tamalanrea Health Center In Makassar. - Hadijah Hadijah; Rizky Auliah Juniarti (Jurnal EduHealth, 2023)
Pregnant women's satisfaction with ANC services is one of the factors that influence pregnant women to make repeat visits to check their pregnancy. Antenatal care is the most important component of health services to reduce maternal and infant mortality. The success of antenatal care efforts depends on health workers and the participation of pregnant women themselves. The purpose of this study was to identify pregnant women's satisfaction with ANC services and the relationship between pregnant women's satisfaction and the regularity of antenatal check-ups. The research design used was "descriptive" research with a Cross Sectional Study design conducted on all pregnant women at the Tamalanrea Makassar Health Center from June 20 to July 20, 2022 with a total sample of 67 people. Sampling technique by means of purposive sampling and referring to the questionnaire. Data processing and data analysis with the SPSS program. The results showed that pregnant women's satisfaction with antenatal care in the Satisfied category and regularity in the regular category. Analysis of the relationship between satisfaction with antenatal care and regularity of antenatal checks with the chi square test showed a significant relationship with X²hit> X²α.db. From the results it is recommended to pregnant women to continue to carry out antenatal care at available health facilities and for health workers to continue to provide quality information and midwifery services.